DEVELOPMENT OF SOCIAL ANXIETY SCALE FOR UNIVERSITY STUDENTS (SAS-US) FOR UNIVERSITY STUDENTS IN JAKARTA - Laurentia Maria; Hoshael W. Erlan (MANASA, 2017)
Presence of interpersonal evaluation in day-to-day college situations indirectly triggers social anxiety in some students. It inhibits the students to look for help. The objective of this research is to develop a new scale to help identify social anxiety in university students and prevent it from developing to social anxiety disorder (SAD). Self-presentation theory by Mark Leary was used to define the construct in Social Anxiety Scale for University Students (SAS-US). The scale was given in the forms of online and hardcopy questionnaires. Total participants for both try out and field procedures are 258 students from different universities, based on convenience sampling technique. Out of 147 items constructed, only 124 items were deemed fit for the field procedure. Data of 158 students from field procedure were eligible for further analysis. Validity test results based on construct validity indicated that Social Anxiety Scale for University Students (SAS-US) valid internally, with 72 items decided as final items. This scale was also considered quite reliable (124 items; α = 0.93) through Cronbach’s Alpha (α). Further research and development of this scale should add an external validity procedure.